Beans, Brands, and Beyond: Exploring the Impact of Social Dynamics on Coffee Shop Purchases in Bandung - Andhi Sukma; Fansuri Munawar; Aditya Yudanegara; Keni Kaniawati; Rini Handayani; Sri Wilujeung SP (Cita Konsultindo Research Center, 2024)
This study examines the influence of brand image, lifestyle and social class on customers' purchasing decisions in the competitive coffee shop industry in Bandung. The research aims to investigate the relationships between these variables, perceived value and actual purchase behaviour. Using a quantitative descriptive approach, data from consumers in the city of Bandung are analysed. The results indicate that brand image significantly influences purchase decisions, while lifestyle and social class play an important role in shaping perceived value. Perceived value acts as a crucial mediator between these factors and consumer behaviour. The study highlights the importance of understanding different consumer segments and tailoring marketing strategies to their culinary preferences. These findings provide valuable insights for industry practitioners seeking to enhance consumer engagement and drive business growth in the coffee shop market.